State-of-the-art on monolingual lexicography for Norway (Bokmål and Nynorsk) - Oddrun Grønvik; Sturla Berg-Olsen; Marit Hovdenak; Knut E. Karlsen (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
Monolingual lexicography for Norwegian started some decades after political independence from Denmark in 1814. Since 1885 two written standards have been recognized, one based on Danish as spoken in Norway (today Bokmål), and one based on the Norwegian vernacular (Nynorsk). Both are fully described in major scholarly dictionaries, now completed and freely available on the web. Both receive some public funding, with a view to further development. Because of frequent orthographic revisions, at first aimed at bringing the written standards closer to each other, spellers dominated the market through most of the 20th century. Today linguistic stability is aimed for, incorporating only such changes in the written standards as are supported by general usage. The first general monolingual defining dictionaries Bokmålsordboka and Nynorskordboka, covering the central vocabulary of each written standard, were first published as parallel volumes in 1986, and are now undergoing revision at the University of Bergen in cooperation with the Language Council of Norway. These dictionaries are now stored in databases, are available on the web and as a free smartphone app. Public funding of monolingual mother tongue lexicography is seen as an investment in essential linguistic infrastructure, as is bilingual lexicography between the Nordic languages and Norwegian, while other bilingual lexicography is dealt with by private publishers.